The Tapestry of Postgraduate Supervision Cultures in Malaysia: Narrative Insights - Sahar, Rafidah; Abdullah, Nur Nabilah; Emaliana, Ive (IIUM Press International Islamic University Malaysia P.O. Box 10, 50728 Kuala Lumpur, 2024)
Supervision in higher education is a complex endeavour whereby its outcome is influenced by the standard of enthusiasm, academic excellence, and interpersonal relationships between supervisors and students. Although there is a growing body of literature on supervision, it remains a multidimensional and complicated phenomenon, with little empirical study on the activities involved. Previous studies have found that supervisors’ research credibility and issues such as mismatches in expectations between supervisors have been identified as significant factors affecting the postgraduate experience. Moreover, given how globalisation and internationalisation movements have affected and continued to transform the higher education landscape in recent decades, studies on postgraduate supervision are more significant than ever. Thus, more studies on supervision are needed to address the more complex and diverse difficulties that have arisen due to the changing student demographics and the increasing complexity of supervisory roles and relationships.